The underestimated role of plant root nitric oxide emission under low-oxygen stress - Welle, Marcel; Niether, Wiebke; Stöhr, Christine (Frontiers in Plant Science, 2024)
The biotic release of nitric oxide (NO), a greenhouse gas, into the atmosphere contributes to climate change. In plants, NO plays a significant role in metabolic and signaling processes. However, little attention has been paid to the plant-borne portion of global NO emissions. Owing to the growing significance of global flooding events caused by climate change, the extent of plant NO emissions has been assessed under low-oxygen conditions for the roots of intact plants. Each examined plant species (tomato, tobacco, and barley) exhibited NO emissions in a highly oxygen-dependent manner. The transfer of data obtained under laboratory conditions to the global area of farmland was used to estimate possible plant NO contribution to greenhouse gas budgets. Plant-derived and stress-induced NO emissions were estimated to account for the equivalent of 1 to 9% of global annual NO emissions from agricultural land. Because several stressors induce NO formation in plants, the actual impact may be even higher.